Mencari Solusi Kritis di Tengah Krisis - Puji Hariyanti (Jurnal Komunikasi)
What an organization does and says in a crisis situation can permanently influence the organization's image. Crisis communication plans can be supplementary to or part of the crisis management plan. Many believe that a crisis communication plan is key to survival of an organization-knowing what to say, when, and to whom. Crisis communication team plays a critical role because the public has a great desire for knowledge in crisis situations.